Early Warning and Quick Response: Accounting in the Twenty-First Century - Mosso, David; SACK, ROBERT J. (The Accounting Review, 2010)
This book contends that the current accounting model, which is used worldwide, and the current accounting standard setting process are seriously deficient. The book describes the deficiencies in an historical context and proposes two complete new models to correct the deficiencies. One is an accounting model called the 'wealth measurement early warning model'. The other is a standard setting process model called the 'quick response model'. The new models are revolutionary and controversial. They are revolutionary in the sense of imposing extensive changes on the accounting establishment, but also because they have three characteristics that are totally absent in the current system: they are simple to understand and apply; they are quick to answer questions about new situations; and, they are reflective of economic events as they occur.